Implementation of Differentiated Learning and Development of English Teaching Materials within the Context of the Merdeka Curriculum - Karim, Luqman Nur; Solikhah, Imroatus; Saputri, Avida Pramayshela; Prayitno, Mustofa Aji (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
Differentiated learning is a vital strategy in addressing student diversity and creating an inclusive learning environment, however, its implementation often faces challenges in effectively meeting the diverse needs of students. This research aims to explore the implementation of differentiated learning and developing English language teaching materials within the context of the Merdeka Curriculum. The study was conducted in the second semester of Grade X at Madrasah Aliyah YPIP Panjeng. The research methodology employed is qualitative analysis of the steps taken by English teachers in designing materials that are responsive to the needs and abilities of students. Exploration of student learning outcomes evaluation and monitoring of the learning process is also conducted to understand the impact of implementing differentiated learning. The results indicate that differentiated learning provides significant benefits in enhancing student understanding and creating an inclusive learning environment. However, challenges such as resource limitations and varying assessments for each student are also identified. From this research, it is concluded that appropriate training and support for teachers, development of diverse learning resources, and ongoing evaluation of the learning process are necessary to enhance the effectiveness of implementing differentiated learning. These measures are expected to strengthen inclusive and sustainable learning approaches at Madrasah Aliyah YPIP Panjeng.